New Approaches to Aluminum Integral Foam Production with Casting Methods - Ahmet Güner; Mustafa Merih Arıkan; Mehmet Nebioglu (Metals, 2015)
Integral foam has been used in the production of polymer materials for a long time. Metal integral foam casting systems are obtained by transferring and adapting polymer injection technology. Metal integral foam produced by casting has a solid skin at the surface and a foam core. Producing near-net shape reduces production expenses. Insurance companies nowadays want the automotive industry to use metallic foam parts because of their higher impact energy absorption properties. In this paper, manufacturing processes of aluminum integral foam with casting methods will be discussed.